2015
DOI: 10.1186/s13058-015-0528-9
|View full text |Cite
|
Sign up to set email alerts
|

Perhexiline promotes HER3 ablation through receptor internalization and inhibits tumor growth

Abstract: IntroductionHuman epidermal growth factor receptor HER3 has been implicated in promoting the aggressiveness and metastatic potential of breast cancer. Upregulation of HER3 has been found to be a major mechanism underlying drug resistance to EGFR and HER2 tyrosine kinase inhibitors and to endocrine therapy in the treatment of breast cancer. Thus, agents that reduce HER3 expression at the plasma membrane may synergize with current therapies and offer a novel therapeutic strategy to improve treatment.MethodsWe de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…A mixture of anti-EGFR monoclonal antibodies that target different EGFR epitopes and increase EGFR ubiquitination and degradation in a CBL-independent manner led to improved efficacy of anti-EGFR therapy [24]. Finally, small molecules, such as the anti-anginal drug perhexilline, promote HER3 internalization and further ubiquitination, leading to inhibition of tumor growth [56]. …”
Section: Discussionmentioning
confidence: 99%
“…A mixture of anti-EGFR monoclonal antibodies that target different EGFR epitopes and increase EGFR ubiquitination and degradation in a CBL-independent manner led to improved efficacy of anti-EGFR therapy [24]. Finally, small molecules, such as the anti-anginal drug perhexilline, promote HER3 internalization and further ubiquitination, leading to inhibition of tumor growth [56]. …”
Section: Discussionmentioning
confidence: 99%
“…In particular, most of the attention is focused on the rate-limiting enzyme of FAO, the carnitine palmitoyltransferase 1 (CPT1). CPT1 can be pharmacologically targeted by drugs like Etomoxir and Perhexiline or the novel compound Avocatin B, with promising results in vitro and in preclinical studies [135,[138][139][140][141][142].…”
Section: Targeting the Fatty Acid Oxidationmentioning
confidence: 99%
“…Although perhexiline maleate has been reported to be a calcium antagonist it was demonstrated that this drug concurrently administrated with doxorubicin also enhanced doxorubicin inhibition of proliferation of the anthracycline-resistant P388 cell sub-line in a reversible way 20 21 . Recently, it has been reported that perhexiline is also a HER3 ablation modulator that inhibits breast cancer cell proliferation in vitro and in vivo, having a synergistic inhibitory effect with lapatinib on tumor growth 34 . Nonetheless, the anti-cancer mechanism of perhexiline remains still unclear.…”
Section: Discussionmentioning
confidence: 99%